Depolarization as Driving Force in Antiferroelectric Hafnia and Ferroelectric Wake-Up - Lomenzo, Patrick D; Richter, Claudia; Mikolajick, Thomas; Schroeder, Uwe (ACS applied electronic materials, 2020)
Antiferroelectricity and wake-up observed in thin hafnium-oxide-based ferroelectrics are examined from the viewpoint of a macroscopic, quantitative model incorporating depolarization effects. Depolarization fields arising from finite screening, a nonferroelectric interface, and a ferroelectric/paraelectric phase mixture are shown to directly impact the switching properties and shape of ferroelectric hysteresis. Charge injection and trapping are used to demonstrate how the progressive stressing of a ferroelectric dead layer results in improved switching with electric-field cycling. The description of ferroelectric hysteresis is applied to HfO2-based ferroelectrics where the longstanding debate concerning wake-up cycling and antiferroelectric properties can be shown to be driven by depolarization mechanisms. The calculated hystereses combine quantitative accuracy, simplicity, and compatibility to multiple microscopic interpretations that show depolarization fields can be the driving force of a field-induced first-order phase transition underlying antiferroelectric behavior.